Mainstreaming `gender' and `integration' needs in human development initiatives: Asian and African migrant women's integration in Europe - Muhammad Wajid Tahir; Rubina Kauser (International Migration, 2022)
The current study examines the inclusion of `gender' in the policies/legislation relating to the human development of women migrants (from Asian and African origins) and their impact on six determinants of migrant's gender ideology in two different European gender regimes: Germany and Sweden. The study is conducted in four stages: (1) thematic analysis of different conventions and recommendations of the UN, ILO, and EU, (2) latent analysis of selected policies/legislation, (3) survey of women migrants, and (4) expert interviews. Exposure to relatively egalitarian gender regimes through migration has brought positive changes in all determinants of the gender ideology of migrants, except domestic chores and caregiving responsibilities. Inclusion of a missing `gender' perspective in relevant measures can expedite smooth integration of migrants, but lack of political commitment, scarcity of financial resources, the absence of gender experts, and lack of coordination between line ministries/agencies are salient barriers to its `inclusion' in both countries.
Keywords: 300